Viability of Lactobacillus bulgaricus and Streptococcus thermophilus in Encapsulated Probiotic Candy With Freeze-Dry Method - Agus Sutandi; Haryanto Haryanto; Eni Kusumawati (Scientiae Educatia: Jurnal Pendidikan Sains)
The level of viable cell count in probiotic candy, based on WHO standard is >106 CFU/ml or >106 CFU/g. Meanwhile, information on the bacterial viability of probiotic candy according to WHO standards is still limited.  The experimental study was conducted to discover the viability of Lactobacillus bulgaricus and Streptococcus thermophilus in encapsulated probiotic candy. Encapsulants consisted of maltodextrin, gum, corn starch, and skim milk. Encapsulation of probiotic bacteria used freeze-dry method. Probiotic candies were stored at room temperature for 14 days in an aerobic condition. The viability of probiotics candy was tested and the results showed significance for each type of encapsulation (p<0.05). The gum and corn starch encapsulations showed bacteria  viability that met WHO standards for functional foods, which ranged from 20,333,333±7,637,626to 31,553,333±2,741,894 CFU/g (>106 CFU/g). The most preferred encapsulant in terms of taste, texture, and aroma was identified as skim milk encapsulation. Further research on the long-term storage of probiotic candy and the viability of probiotic candy bacteria in the gastrointestinal tract (in vivo) is needed.